Who Shapes the Politics of Expertise? Co‐Production and Authoritative Knowledge in Thailand's Political Forests. Issue 4 (20th May 2019) - Forsyth, Tim
Abstract: Expert environmental knowledge has often been described as a governmental rationality that reduces political debate and facilitates state control. In this paper, I argue instead that this line of reasoning simplifies how knowledge gains political authority, especially when expertise is shared and left unchallenged by diverse actors, including those in conflict with each other. Using the framework of co‐production from Science and Technology Studies (STS), I apply this argument to conflicts over the supposed watershed functions of forests in Thailand, where simplified narratives about the impacts of land use on water supply are used as justifications for territorialisation and restrictions on forest land. In particular, I focus on local resistance to the proposed Kaeng Sua Ten dam in northern Thailand in order to demonstrate how protestors have deliberately reproduced formal expertise to empower themselves, but by so doing also reinforcing simplified visions of watershed science and community culture. I argue that exposing the co‐production of authoritative knowledge and visions of social order offer greater opportunities for understanding the role of expertise as a political force than analysing competing assemblages based on oppositions of state‐led expert knowledge and traditional local practices.